The analysis of age density dynamics of bone tissue of the different parts of lower jaw in preschool children. - Chaykovska, S. Y. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Movement of permanent teeth mostly depend on the quality of bone tissues jaws, universal indicator of which, according to different authors, is bone mineral density. Modern ray examination methods of dental patients allow us to determine this indicator, particularly in the practice of dentistry for this purpose using the method of dental radiovisiography. Objective. The purpose of our study was to identify regularities of age density dynamics of different parts of the body of the mandible in preschool children. Methods. To achieve the goal, we have examined 100 children aged 6 years (including 50 girls and 50 boys) without dental pathology with physiological development of the maxillofacial area and without disease history, which could affect the bone tissue. All the patients were divided into 5 age groups - children of 6 months, to 1 year, 2 years, 4 years and 6 years, 10 children in each group. Radiovisiographic examination was conducted, density of bone tissue was determined in conventional units grayness (CUG). Results. It was found out that in girls the density of the main body part of the mandible was growing up to 1 year and gradually reduced over the next age periods, falling to a minimum meaning in children of 6 years. In the central area of collar parts the investigated index has a minimum value at 6 months of age, gradually increasing up to 2 years, reaching a maximum value and decreases to 6 years. In the lateral area of collar section of the lower jaw in girls the density of bone tissue falls to a minimum value at the age of 1 year and gradually increases in next age periods, rising to a maximum value at 6 years old. In boys, the density of the main body part of the mandible rises to a maximum meaning at the age of 1 year, falls to the minimum level at the age of 4 years and increases again at 6 years of age. In the central area of the collar part of body of the mandible the investigated indicator is the lowest rate at 6 months of age, increases to 2 years of age, somewhat reduces in 4-year-olds and rises to a maximum of 6 years old. In the lateral area of collar side of the body of the mandible bone tissue density is reduced to the minimum level at the age of 1 year with subsequent increase to a maximum of 6 years. Conclusion. Peculiarities of the ratio of bone tissue density of different parts of the mandible body in children of both sexes of preschool age must be taken into account before stomatologic interventions. These data also will help to predict physiological course of teeth changes and the formation of permanent occlusion and prevent anomalies of teething.